Human Impact on the Spatiotemporal Evolution of Beach Resilience on the Northwestern Yucatan Coast - Torres-Freyermuth, Alec; Medellín, Gabriela; Salles, Paulo (Frontiers in Marine Science, 2021)
The northern Yucatan peninsula is prone to coastal flooding and erosion owing to its low-land elevation and high exposure to storms. Therefore, it is important to assess the capability of the beach-dune system to resist, recover, and adapt from storms in the context of coastal development and climate change. This work aims to investigate the role of human impacts on the spatiotemporal evolution of the Coastal Resilience Index (CRI) in the area. The study is conducted on a prograding micro-tidal beach located on the vicinity of coastal structures. Beach and dune morphometrics, characteristic beach parameters, and maximum shoreline recession were determined from the analysis of beach profiles undertaken along a 2-km straight of coastline during the 2015-2020 period. Moreover, the maximum extreme water levels were estimated using in situ data and numerical models. This information is employed to assess the alongshore and temporal variability of the beach resilience. The results suggest that the beach and dune morphology present alongshore and temporal variability due to the human impacts associated to the dune degradation and the presence of coastal structures. The analysis shows that coastal resilience has been increasing over the past years but present significant alongshore variations. High CRI values were found at beach transects presenting low anthropogenic impact, whereas low resilience was observed at transects with a degraded dune or located in the vicinity of coastal structures regardless of presenting high progradation rates. The observed beach response during the passage of recent tropical storms is consistent with the CRI values.